Isolated prenatal ultrasound findings predict the postnatal course in gastroschisis - Frybova, Barbora; Vlk, Radovan; Kokesova, Alena; Rygl, Michal (Pediatric surgery international, 2015)
PURPOSE: The aim of the study was to identify which prenatal ultrasonographic findings in fetuses with gastroschisis correlate with complicated postnatal outcome. METHODS: Ultrasound findings at the 30th week of pregnancy and medical reports were statistically analyzed to identify independent prenatal ultrasonographic predictors of postnatal outcome. RESULTS: Completed prenatal data were gathered from 64 pregnancies. Prenatal intra-abdominal bowel dilatation (cutoff 10 mm) correlated with the presence of atresia (p < 0.01), longer administration of parenteral nutrition, extended hospital stay (median 53 vs. 21 days; 68 vs. 36 days, both p < 0.05), and greater number of additional surgical procedures (p < 0.05). Infants with antenatal presence of thickened bowel wall (greater than or equal to 3 mm) required longer administration of parenteral nutrition (median 34 vs. 20 days; p < 0.01) and prolonged stay (median 44 vs. 37 days; p < 0.05). Presence of oligohydramnion (amniotic fluid index below 8 cm) was connected with longer administration of parenteral nutrition in newborns (median 30 vs. 16 days; p < 0.05). CONCLUSION: The isolated presence of oligohydramnion with amniotic fluid index below 8 cm, thickened bowel wall equal to or more than 3 mm and the prenatal intra-abdominal dilatation with 10 mm cutoff had significant predictive value for the adverse postnatal outcome of patients with gastroschisis.
Keywords: reprodukovatelnost výsledků; Infant, Newborn; mužské pohlaví; Retrospective Studies; ultrasonografie prenatální; Male; retrospektivní studie; gastroschiza; Reproducibility of Results; Humans; Female; Prognosis; novorozenec; lidé; ženské pohlaví; těhotenství; mladiství; postnatální péče; prognóza; Young Adult; Ultrasonography, Prenatal; Adolescent; mladý dospělý; dospělí; Pregnancy; Adult; Postnatal Care; Gastroschisis